2008
DOI: 10.1007/s12325-008-0005-2
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of thoracic epidural analgesia for laparoscopic cholecystectomy

Abstract: The epidural technique provided a significant effect on postoperative pain in patients undergoing laparoscopic cholecystectomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 33 publications
0
27
0
1
Order By: Relevance
“…IV-PCA, while useful, has the side effects of opioids [4]. Though the analgesic effect of patient-controlled thoracic epidural analgesia is better than that of IV-PCA [5], there is a potential risk of dural puncture, infection, and epidural hematoma, as well as muscle weakness, which may cause even paralysis of respiratory muscles [6,7]. An intraperitoneal injection of local anesthetics also has the problems of insufficient pain control and short duration of analgesia [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…IV-PCA, while useful, has the side effects of opioids [4]. Though the analgesic effect of patient-controlled thoracic epidural analgesia is better than that of IV-PCA [5], there is a potential risk of dural puncture, infection, and epidural hematoma, as well as muscle weakness, which may cause even paralysis of respiratory muscles [6,7]. An intraperitoneal injection of local anesthetics also has the problems of insufficient pain control and short duration of analgesia [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…Regional anesthesia in the form of epidural analgesia has been found to be an effective way of improving pain control after laparoscopic cholecystectomy. 29 However, in liver resections, transient impairment of liver function may occur and possibly increase the risk of epidural hematoma. 1Y6 Therefore, epidural analgesia has been controversial.…”
Section: Discussionmentioning
confidence: 99%
“…Low incidence in their study could be attributed to antiemetic prophylaxis with metoclopramide and ondansetron, avoidance of hypotension, adequate pain control and avoidance of postoperative parenteral opioids medication. Demet et al (19) found that epidural group had a lower incidence of nausea/vomiting and sedation compared with intravenous analgesia.…”
Section: Fmentioning
confidence: 99%
“…Also resting postoperative VAS pain score at discharge was 4.7 ± 2.5 in general anesthesia versus 2.2 ± 1.6 in epidural anesthesia. Demet et al (19) found that mean pain scores in the epidural group (0.16±0.31) were lower than those in the intravenous group (3.13±1.75), and concluded that epidural analgesia with a bupivacaine/fentanyl combination provided a statistically and clinically…”
Section: Ementioning
confidence: 99%